Precision fertiliser application in Asia - CGIAR Research Program on Rice (2019)
Prototype applicators provided by Lehner GmbH to IRRI and national partners in all countries and tested in research fields. Data on evenness of application established and several tool carrier platforms tested (hand tractor, transplanter, four wheel tractor). Used regularly at IRRI Experiment Station for research trials.